The Crisis of Religious Identity in Sixteenth Century Central Asia The Centrality of ʿAlidism in the Maẓhar al-ʿAjāʾib - Shanazarova, Aziza (2023)
The present study explores the centrality of ʿAlidism in the religious profile of a Sufi community active in the early sixteenth century in Mawarannahr, which was at the center of the ongoing major religio-political transformations in the aftermath of the decline of the Timurid dynasty. This community was led by a female Sufi master celebrated as Aghā-yi Buzurg (the Great Lady). The misfortunes faced by Aghā-yi Buzurg and her followers during this critical transitional period was related to her group’s upholding the Timurid-era tradition of ʿAlid devotion under the early Shibanid rule. The public proclamation of pro-ʿAlid sentiments in post-Timurid Central Asia became dangerous in the early sixteenth century when the veneration of ʿAlī and his descendants started being associated with sympathies toward the Shiʿi Safavids. It is remarkable that Aghā-yi Buzurg's public career as a leader of the Sufi community consisting of male and female disciples was not the main factor provoking the attacks against her community, but instead, it was their admiration of ʿAlī and his descendants.
Keywords: Central Asia; Sufism; Sunni-Shiʿi antagonism; the sixteenth century; ʿAlidism